How does indian gold price react to the changes in real exchange rates? - D, Lazar; S, Maria Immanuvel (Journal of Management and Science, 2012)
This study investigates the relationship between the Indian gold price and the real exchange rates of major international currency and how does Indian gold price reacts to the exchange rates of these currencies. The data set consists of monthly gold prices from Indian market and the real exchange rates of major currencies like USD, Euro, Yen and INR for the period from 1994:01 to 2011:12. The relationship and reaction is tested through the Johansen cointegration test, Granger causality test and VAR models like Impulse response function and Variance Decomposition. It is found that the Indian gold prices have long run relationship with the real exchange rates of major currencies and it is also found that the Indian gold prices are caused by the real exchange rate of Yen but the vice versa does not exist. The Indian gold prices react positively to the shocks from Yen and negatively to the INR.